Assessment of the genetic diversity and population structure of rice genotypes using SSR markers. (2nd January 2020) - Suvi, William Titus; Shimelis, Hussein; Laing, Mark; Mathew, Isack; Shayanowako, Admire Isaac Tichafa
ABSTRACT: Genetic diversity is a pre-requisite for rice ( Oryza sativa L.) breeding and population development. Hence, the objective of this study was to assess the genetic diversity and population structure of 54 rice accessions using 14 polymorphic simple sequence repeats (SSR) markers to select unique parents for breeding. Data analysis was based on marker and population genetic parameters. The mean polymorphic information content (PIC) was 0.61 suggesting high polymorphisms for the selected SSR markers among the rice accessions. The population structure revealed a narrow genetic base with only two major sub-populations. Analysis of molecular variance revealed that only 30% of the variation was attributed to population differences while 47% and 23% were due to variation among individuals within populations and within individual variation, respectively. The genetic distance and identity among genotypes varied from 0.083 to 1.834 and 0.159 to 0.921, respectively. Dendrogram grouped the genotypes into three clusters with wide variation among the accessions. The study established the existence of considerable genetic diversity among the tested 54 accessions. The selected genetic resources will be useful resources for rice breeding in Tanzania or other African countries.